2016
DOI: 10.21037/tlcr.2016.12.06
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell lung cancer (NSCLC) and central nervous system (CNS) metastases: role of tyrosine kinase inhibitors (TKIs) and evidence in favor or against their use with concurrent cranial radiotherapy

Abstract: Central nervous system (CNS) metastases, including brain metastases (BM) and leptomeningeal metastases (LM) represent a frequent complication of non-small cell lung cancer (NSCLC). Patients with BM comprise a heterogeneous group, with a median survival that ranges from 3 to 14 months. However, in the majority of patients, the occurrence of CNS metastases is usually accompanied by severe morbidity and substantial deterioration in quality of life. Local therapies, such as whole brain radiotherapy (WBRT), stereot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 85 publications
1
27
0
1
Order By: Relevance
“…There is no recommendation in the current guidelines and no evidence regarding the concurrent administration of cranial radiotherapy and ALK-TKI (20). In our study, both of the patients who concurrently underwent WBRT with ALK-TKI suffered from grade 3 otitis media as a consequence of the concurrent treatment.…”
Section: Discussionmentioning
confidence: 66%
“…There is no recommendation in the current guidelines and no evidence regarding the concurrent administration of cranial radiotherapy and ALK-TKI (20). In our study, both of the patients who concurrently underwent WBRT with ALK-TKI suffered from grade 3 otitis media as a consequence of the concurrent treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Regarding benefits, a combination of EGFR-TKIs and radiotherapy has been hypothesised to result in radiosensitisation and increased permeability of the BBB to EGFR-TKIs [16,17]. Many meta-analyses and retrospective studies regarding the combination of EGFR-TKIs with radiotherapy have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have reported no survival benefit [23][24][25][26]. Thus, the optimal treatment combination or sequence for brain metastasis remains controversial [16]. Besides, these studies had many limitations, owing to the retrospective analyses, such that the majority did not examine the late effects of radiotherapy on neurocognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, whole brain radiotherapy is controversial at present. Especially for those patients with poor general medical condition, best support care has similar efficacy as whole brain radiotherapy [5,[28][29][30]. It was revealed that radiotherapy times are negatively related with the prognosis.…”
Section: It Is Recommended By National Comprehensive Cancermentioning
confidence: 99%